Analisis Faktor Faktor yang mempengaruhi Tingkat Keberterimaan Masyarakat terhadap Penerapan Cukai pada Minuman Berpemanis - Eksa Ridwansyah; Destia Pentiana; Irawan Irawan (Penerbit Goodwood, 2022)
Purpose: This study aims to analyze the level of public acceptance and the factors that influence public acceptance of the planned implementation of excise duty on sweetened drinks. Method: The research variables are: 1. Perceptions of consumption need to be controlled, 2. Perceptions of its distribution need to be monitored, 3. Perceptions of its use can have a negative impact on society or the environment 4. Perceptions of its use need to impose state levies for the sake of justice and balance, 5. The level of acceptance of excise duty on sweetened drinks. The sample of this research is people who have bought sweetened drinks and are more than 17 years old. Data collection was carried out by distributing questionnaires with incidental sampling techniques. The analysis technique used is multiple linear regression analysis. Results: Respondents responded to filling out the questionnaire totaling 63 people, the results of the study were: Perceptions of consumption and circulation have no effect on the Level of support for the government to impose excise rates on sweetened drinks. Meanwhile, the variables Perceived Impact and levies have a significant effect on the level of support for the government to impose excise rates on sweetened drinks. Overall the independent variables namely Perceived Consumption, distribution, impact and charges have a significant effect on the level of support for the government to impose excise rates on sweetened drinks. Contributions: This exploration has contributed to the enrichment of aspects of the public acceptance of excise duty on sweetened drinks literature.